MENELUSURI JEJAK SEJARAH MARKAS BESAR ANGKATAN DARAT KE-25 KEKAISARAN JEPANG DI PULAU SUMATERA - Vika Afriani Putri (Hadharah: Jurnal Keislaman dan Peradaban, 2021)
Based on the long history of Indonesia, the Dutch and Japanese Colonials once ruled the land of Indonesia for 350 years by the Netherlands and Japan for 3.5 years. To improve the patriot spirit of the nation, it is very important to learn about the past, how cruel the colonization was and the struggle of the nation's heroes for Indonesian independence. Japanese power in Indonesia can be seen through historical evidence in the form of Japanese military defense buildings scattered in areas in Indonesia, especially on the island of Sumatra. Japan chose its military defense center in Bukittinggi as the headquarters of the 25th Army. The research method used in the form of historical research methods such as heuristics, is a stage of collecting historical data, critique that is critique of the data that has been obtained, interpretation gives an opinion about history theoretically and historiography develops a history as a discipline and archaeological research methods such as Observation stages in collecting related data through a review of the literature or a direct visit in the form of objects or buildings, description processing and providing an explanation of the data obtained and an explanation of writing research results. The Japanese military defense buildings located in Bukittinggi, Agam and the surrounding area are the Japanese Bunkers in the Sariak River, Taluak, Tiku and the Muko-Muko area of Tanjung Raya Maninjau. Through physical evidence that the true headquarters of the Army's 25th centered in New York City as one of the strategic areas for surveillance and attack enemies as a central military command control central Sumatra, Aceh and northern Malacca Strait.